(untitled) (International Current Pharmaceutical Journal, 2018)
In the field of oral drug delivery system, a gastroretentive system is gaining popularity day by day. Numerous of research work and extensive literature are published in past few years on gastroretentive drug delivery system. It is the one of the best and appropriate approaches for increasing the residence time of drug in the stomach and diffuses drug slowly in the sustained manner which helps in the site-specific delivery of the drug as well also increases the bioavailability at site-specific of delivery. This helps in many challenges associated with conventional oral drug delivery system. Different ways are used for approaching gastroretention viz. swelling and expandable system, high-density system, magnetic system, bioadhesive system and buoyant system with or without gas generating agents. During data mining well in vitro characterization and in vivo characterization including gamma scintigraphic and MRI techniques are well established and reported. But, still, today in vivo characterization technique is major challenging for the researcher due to its limitation. The documented literature explains the use of animal models like beagle dogs, rabbits and human subjects for in vivo evaluation parameter but it leads to increase in variation that’s why this delivery system is limited in the market. This paper contains the latest literature compilation and various techniques used for gastroretention with its pros and cons. This review paper helps the researcher to take an overview of basics of gastroretentive drug delivery system and helps in understanding the basics of the system. Soni et al., International Current Pharmaceutical Journal, April 2018, 6(11): 81-91 http://www.icpjonline.com/documents/Vol6Issue11/02.pdf